Everyday Digital Citizenship among Slovak University Students: Ethics, Privacy, and Social Responsibility on Social Media - Rendy Gobel; Martin Vaculčiak; Kristína Tučeková (Universitas Negeri Gorontalo, 2026)
This study explores digital citizenship practices among Slovak university students in their use of social media, with particular attention to communication ethics, privacy, and social responsibility. Using a qualitative descriptive case study design, data were collected through semi-structured interviews, in-depth observation, and documentation involving three Slovak university students who actively used Instagram, YouTube, and TikTok. The data were analysed thematically through transcription, repeated reading, initial coding, theme development, and interpretive synthesis. The findings show that social media functions as an everyday space for communication, information seeking, social connection, entertainment, and learning. Participants’ digital citizenship practices were reflected in communication ethics centred on the principle of not harming others, including avoiding insults, harsh language, cyberbullying, and personal attacks. Privacy awareness was also evident through the use of private accounts, close-friends features, selective sharing of personal information, and reluctance to post images of others without consent. However, students’ social responsibility remained largely personal and protective, as they tended to ignore or block problematic accounts rather than engage in collective or corrective action. The study concludes that digital citizenship among the participants has developed at the level of interpersonal ethics, privacy protection, and self-control, but requires further strengthening in terms of active participation and collective social responsibility in digital spaces.